Perlindungan Hukum Terhadap Anak Korban Kekerasan Seksual di Kabupaten Halmahera Selatan - Laure, Muhammad Gamal T; Stomer, Fandi (Jurnal Ilmiah Wahana Pendidikan, 2025)
Sexual violence against children is a serious form of human rights violation and has long-term impacts on children's growth and development. In South Halmahera Regency, this phenomenon still often occurs, especially in areas with limited access to information, social supervision, and legal protection. This study aims to analyze the form and effectiveness of legal protection for child victims of sexual violence through a case study approach and literature study. This study explores three actual cases that occurred between 2022 and 2024, and examines various regulations and their implementation at the regional level. The results of the study show that although national regulations are adequate, the implementation of legal protection in the regions still faces various obstacles, such as weak victim assistance, slow law enforcement processes, and minimal coordination between institutions. This study recommends strengthening regional policies, increasing the capacity of law enforcement officers, and providing integrated, child-friendly assistance services.